Hypoxia decreases macrophage glycolysis and M1 percentage by targeting microRNA‐30c and mTOR in human gastric cancer. Issue 8 (12th July 2019) - Zhihua, Yun; Yulin, Tan; Yibo, Wang; Wei, Ding; Yin, Chu; Jiahao, Xu; Runqiu, Jiang; Xuezhong, Xu
Abstract: Macrophages are essential inflammatory cells which regulate the features of immune reactions within tumors. Many studies have reported their regulatory roles in immunity through cytokines and cell signaling. However, relatively few studies have focused on their metabolic features and mechanisms. We aimed to determine the signaling pathway regulating cell metabolism and the mechanism related to the regulation of human tumor‐associated macrophages (TAMs) in gastric cancer (GC). Tumor‐infiltrated macrophages were isolated from human GC tissues using magnetic beads, gene transcription was determined by real‐time PCR, protein expression was monitored using western blots, metabolites were determined using HPLC, and transcriptional regulation was analyzed by the luciferase‐based reporter gene system. A significant decrease in microRNA (miR)‐30c and an increase in regulated in development and DNA damage responses 1 (REDD1) were detected in human GC TAMs, the transcription of miR‐30c was negatively correlated with REDD1. MicroRNA‐30c expression was suppressed by hypoxia‐inducible factor‐1α activation and related to decreased mTOR activity as well as glycolysis in human GC TAMs. Hypoxia‐regulated miR‐30c downregulated REDD‐1 expression by targeting its 3′UTR. Overexpression of miR‐30c or restored mTOR activity in macrophages with miR‐30c Low expression promoted M1 macrophage differentiation and function in TAMs. Therefore, hypoxia in the human GC microenvironment suppressed the expression of miR‐30c, and decreased mTOR activity as well as glycolysis in GC TAMs, thus inhibiting M1 differentiation and function. These results provide a novel metabolic strategy for tumor microenvironment‐based therapy. Abstract : Hypoxia in the human gastric cancer microenvironment suppressed the expression of microRNA‐30c, and decreased mTOR activity as well as glycolysis in gastric cancer tumor‐associated macrophages, thus inhibiting M1 differentiation and function. These results provide a novel metabolic strategy for tumor microenvironment‐based therapy.